Penggunaan Model Problem Based Learning Untuk Meningkatkan Komunikasi dan Kolaborasi Peserta Didik Kelas X - Annisa Hartiyaningsih; Eko Retno Mulyaningrum; Risno Setiyono (Jurnal Pendidikan Guru Profesional, 2024)
This study aims to improve communication and collaboration of students in class X-3 SMA Islam Sultan Agung 1 Semarang in learning Biology virus material through Problem Based Learning model. Problem Based Learning is a learner-centered learning model, where learners face real problems that require solutions through collaboration and active communication with discussion groups and classmates. This type of research is a class action research (PTK) consisting of two cycles, in each cycle there are two meetings. Each cycle has three stages, namely planning (Plan), implementation (Do), and reflection (See). The subjects in this study were X-3 class students totaling 30 female students. Each research cycle, students were given a problem relevant to the virus material and they were expected to work together in groups to solve the problem. During this process, they had to communicate with fellow group members, discuss, and design solutions to the problem. Data collection techniques used through observation sheets, and documentation as research data. Data analysis was made descriptively qualitative. The results showed that the application of Problem Based Learning can improve students' communication and collaboration skills on virus material. This can be seen from cycle 1 the recapitulation of communication results of 68.60% increased to 80.80% in cycle 2. The increase in collaboration skills from cycle 1 amounted to 71.60% to 89.67% in cycle 2. The conclusion of this study is that by using the Problem Based Learning learning model there is an increase in communication and collaboration skills of students.